Enigmaticolus inflatus sp. nov., a new buccinid species from a methane seep area in the South China Sea (Gastropoda: Neogastropoda) - Zhang, Shuqian; Zhang, Suping; Chen, Hao (Zootaxa, 2020)
During an investigation carried out by the Institute of Oceanology, Chinese Academy of Sciences (IOCAS), two living buccinid specimens were collected from a deep-sea methane seep area in the South China Sea. Observations of the shell, gross anatomy and radular morphology reveal that they represent an undescribed species of the genus Enigmaticolus. In this paper, we describe and illustrate this species as Enigmaticolus inflatus sp. nov. The new species is by general shell shape most similar to Enigmaticolus marshalli Fraussen & Stahlschmidt, 2016 from Kermadec Ridge, New Zealand, but can be distinguished from it by having an inflated shell with reduced spiral sculpture, and by the absence of axial sculpture. Phylogenetic analysis using 636 bp of the cytochrome oxidase c subunit I (COI) gene also supports its systematic placement within Enigmaticolus.